Variasi Sisik Tumbuhan Paku Terestrial di Kampus IPB, Dramaga, Bogor : Variations of Terrestrial Scale Fern on The Campus of IPB University, Dramaga, Bogor - Siti Halimatussadiah; Nina Ratna Djuita; Tatik Chikmawati Chikmawati (Departemen Biologi, Institut Pertanian Bogor, 2023)
IPB Dramaga campus has high biodiversity, one of which is terrestrial ferns. Ferns have scales or hairs that cover the rhizome, petiole and leaf blade. The characteristic of scales can be used in the identification of fern species. The aim of this study was to determine the morphological diversity of terrestrial fern scales collected from the IPB Dramaga campus. The fern scales was observed under a light microscope connected to an indomicro and the density was calculated. The rhizome and petiole scales found in the form of lanceolate, ovate, subulate, linear, and reniform. The tip of the scales varies from thick, and needle-like, thin, and thick. The edges of the scales vary, namely threaded, flat, or banded. The attachments of the base of the scales found were, peltate. pseudopeltate, and basifix. The color of the scales varies from transparent, yellow, light brown, fawn, and dark brown. The scale density ranged from 0.6 to 21.3/mm2. The Pteridaceae have more characteristics in common between their genera than the other two family, but these similarities cannot be used for taxonomic identification and classification, because they are not specific for each genus.